Selected letters of Martha Gellhorn - Gellhorn, Martha 1908-1998 (Holt, 2006)
Spanning the years from 1930 to 1996, the correspondence of the acclaimed journalist chronicles Gellhorn's career from the Spanish Civil War to the end of the Cold War, as well as her turbulent marriage to Ernest Hemingway.
Includes index.
Keywords: Gellhorn, Martha <1908-1998> -- Correspondence; Gellhorn, Martha -- 1908-1998; Geschichte 1900-2000; Authors, American -- 20th century -- Correspondence; Journalists -- United States -- Correspondence; USA; Briefsammlung